PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS PROBLEM BASED LEARNING PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL UNTUK SISWA KELAS VIII SMP/MTs - Yolanda Frastika Yonasri; Sakur Sakur; Zulkarnain Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the limited mathematics learning devices that are in accordance with the 2013 Curriculum. This research purposed is to produce mathematics learning devices such as syllabus, lesson plans, and student worksheets by using problem based learning on linear system with two variables material for the eighth grade of junior high school. The development model used in this research is the 4-D model which consists of the stages of define, design, develop, and disseminate. The learning devices that have been developed were validated by three validators and revised according to suggestions from the validators. The average score of the validation results for the syllabus, lesson plans, and student worksheets are 3.47, 3.50, and 3.61 with very valid categories. The results of this validation indicate that the syllabus, lesson plans, and student worksheets are feasible to be tested. Student worksheets that has been valid is then tried out in small groups. The average score of the small group trial results for student worksheets is 93.67% with very practical category. Based on the results of data analysis and discussion it can be concluded that the syllabus, lesson plans, and student worksheets by using problem based learning on linear system with two variables material for the eighth grade of junior high schoo has fulfilled valid.Keywords: Mathematics Learning device, Problem Based Learning Model, 2013 Curriculum, Linear System With Two Variables, 4-D Development Model.